Die Abhängigkeit der Bodenbildung von der Geomorphologie in Bulgarien - Koinoff, Welin (ERDKUNDE, 1965)
The territory of Bulgaria contains a remarkable variety of different soils which are largely due to the geomorphological conditions. The dependence is particularly interesting in Thrakia, southern Bulgaria. There, a series of tectonic movements during the Quaternary resulted in a differentiation of river deposition according to time, amount and area. Linked with these is a different composition and different age of the parent materials in the various river valleys. The tectonic disturbances resulted in many places in subsidence and faulting which changed the relief and hydrographic conditions and in turn resulted in the formation of a series of new secondary soils as these are closely related to processes of swamp formation, salinisation, drainage and denudation. In connexion with these conditions eight clearly distinguishable, genetically separated soil complexes of different age can be distinguished, composed of primary and secondary soils. The first of these complexes is linked with the oldest products and accumulations of weathered material, i. e. of Pliocene and pre-Pliocene age respectively; the other seven are derived from Quaternary deposits of different age. Although these soil complexes are not related to clearly recognisable river terraces it nevertheless appears that this in fact is the case; owing to subsidence these terraces are, however, not morphologically discernible. Similar conditions are also characteristic of the Transbalkan plains and the basin plains of south-western Bulgaria. Morphologically better distinguishable river terraces can be observed in northern Bulgaria, in the valley of the Danube and those of its tributaries. Whereas there are usually four or five river terraces in the western and central section of the Danube plain, in the south, in the valleys close to the Fore-Balkan, seven river terraces can be distinguished. In this region a clearly pronounced dependence of soils from age and type of the parent material of the different terraces can be observed. The paper related these conditions of the different morphological regions of Bulgaria in greater detail.